In Silico Analysis of Ocimum Basilicum Flavonoids as Natural Antihypertensive Agent on Angiotensin II Type-1 Receptor (AT1R) - Thalib, Amir; Damayanti, Irma Putri (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Despite the efficacy of antihypertensive medications like ARBs, their adverse effects frequently result in suboptimal adherence. This study investigates the efficacy of flavonoids obtained from herbal sources as natural substitutes for traditional antihypertensive therapies. This study employed in silico molecular docking to examine the binding affinity of flavonoids to the angiotensin II type-1 receptor (AT1R) in comparison to standard angiotensin receptor blockers (ARBs), namely Eprosartan, Azilsartan, Irbesartan, Telmisartan, Valsartan, Losartan, Olmesartan, and Candesartan. Docking analysis indicated that the flavonoids exhibited a favorable binding affinity of -8.8 kcal/mol for AT1R. Moreover, ADME and toxicity assessments indicated that flavonoids exhibit advantageous pharmacokinetics and minimal toxicity, with no significant adverse interactions anticipated with primary metabolic enzymes. The structural validation, encompassing Ramachandran plots and ERRAT analysis, affirmed the reliability of the modeled AT1R protein, achieving a quality score of 97.13%. This study concludes that flavonoids derived from Ocimum basilicum exhibit significant potential as natural antihypertensive agents. These findings may facilitate the development of plant-based therapies with minimal adverse effects, enhance treatment adherence, and improve the pharmacological options for managing hypertension.